LARANGAN DEMO OLEH SULTAN HAMENGKU BUWONO X PASCA DEMO 8 OKTOBER 2020 DI YOGYAKARTA - Toni Kurniawan Anna Zakiah Derajat (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
This paper aims to explain the implementation of Article 5 of Law Number 9 of 1998 concerning Freedom to Express Opinions after the demonstration on October 8, 2020 in Yogyakarta, thus giving birth to Sri Sultan Hamengku Buwono X's appeal regarding demonstrations in the perspective of maslahah. This type of research is literature research by conducting various studies that are considered credible with the primary source studied. This research results in a conclusion that freedom to express opinions in public is part of the basis of democracy, which has a role in eradicating corruption, gaps in government, and a last resort in conveying an aspiration. In implementing Article 5 of Law Number 9 of 1998 at the demonstration that took place on October 8, 2020 in Yogyakarta, restrictions are still needed so as not to conflict with Islamic law and laws. The demonstration in Yogyakarta led to anarchism, which led to a response from Sultan HB X. The appeal issued by Sultan HB X can be justified because it considers many things, one of which is security, safeguarding public facilities, and order. This appeal also does not mean to limit, eliminate people's rights, and prohibit them from expressing their aspirations.